Leadership in Public Health: Opportunities for Young Generations Within Scientific Associations and the Experience of the “Academy of Young Leaders” - Gianfredi, Vincenza; Balzarini, Federica; Gola, Marco; Mangano, Sveva; Carpagnano, Lucia Federica; Colucci, Maria Eugenia; Gentile, Leandro; Piscitelli, Antonio; Quattrone, Filippo; Scuri, Stefania; Mantovani, Lorenzo Giovanni; Auxilia, Francesco; et al. (Frontiers in Public Health, 2019)
Comparing to other sectors, scientific leadership dynamics take into consideration different aspects. Besides awards (Nobel Prize or several other) and prestigious affiliations, eventual indicators might be academic roles, fundraising abilities, summits of scientific associations, editor-in-chief of journals or editorial series and, more recently, bibliometric indicators. The peculiar topics of public health encompass interactions with institutions, authorities, politicians, involved in different levels in health policies. This article elaborates these perspectives and the role covered by scientific associations, involved in education, advocacy and intermediation with the institutions and reference for each member of the community. Recently, the Italian Minister of Health has identified parameters to make scientific societies lawfully responsible of guidelines. The role of SItI (Italian Society of Hygiene), EUPHA, ASPHER and WFPHA appears relevant, in national and international contexts, with Italian praiseworthy members constantly achieving leading roles. Considering that few training opportunities aimed to improve research and leadership skills are available, Accademia Lombarda di Sanità Pubblica (ALSP) designed the AYLPH (Academy of Young Leaders in Public Health) program. AYLPH program is a 1-year training to shape leadership skills among young professionals. A set of didactic, theoretical and practice methods was offered. The first module consisted of a winter team-building course, the second was designed to improve literature search abilities, mentorship skills and formulate research questions relevant for public health; the third consisted in attending national and international conferences, and the last aimed to improve communication skills using traditional and new media. Even if the program is still ongoing, participants already achieved some encouraging results. Leadership skills are essential particularly when community’s health is undermined by a sense of distrust in institutions. The new leaders should be able to drive the change, and the program aimed to teach new competencies.